ESTIMASI BILANGAN REPRODUKSI DASAR PENYEBARAN PENYAKIT DEMAM BERDARAH DENGUE DI KOTA BIMA TAHUN 2018 - 2020 - Ariyanto Ariyanto; Ganesha L Putra; Meksianis Z Ndii (J-Icon : Jurnal Komputer dan Informatika, 2021)
In this paper, the mathematical model used is the host-vector model for transmission on of dengue hemorrhagic fever where the host population consists of three compartments, namely susceptible host, infected, and recovered, while the vector population consists of two compartments, namely susceptible vector and infected vector. From this model, an estimate of the basic reproduction number will be constructed with the assumption that the number or humans and mosquitoes infected with the dengue virus grows exponentially with the same growth rate. Applications using field data in the City of Bima obtained an basic reproduction number estimates of . Because the estimated values for the basic reproduction number are greater than one, it illustrates that the spread of dengue hemorrhagic fever in Bima City from 2018 to 2020 is categorized as an epidemic.